APPLICATION OF RESILIENT DENTURE LINING MATERIALS: LITERATURE REVIEW - Mariana Yankova; Todor Peev; Bozhidar Yordanov; Mariana Dimova-Gabrovska; Rangel Todorov (Peytchinski Publishing, 2021)
Clinical cases of excessive bone resorption, presented thin, non-pliable mucosa, exostosis or painful neurogenic points require more specific methods for treatment with removable dentures. Specialized scientific literature discusses various materials and technologies for solving these problems. The use of resilient lining materials (RLMs) for partial and complete dentures is a possible solution if there are clear clinical indications and appropriate selection of the type of material. The purpose of this review is to provide and analyze up-to-date literature data on the use of resilient materials for partial and complete denture lining. Material and Methods: An electronic search in PubMed, Google, EBSCOhost and Science Direct databases was conducted from January to December 2019. Results: Resilient lining materials have a variety of applications. They can be used in complete and all types of partial edentation, i.e. Classes I, II, IV and VI by Kennedy - Popov. The indications for use are different for the two RLMs groups, i.e. temporary (short-term) and permanent (long-term) lining materials. A number of authors have identified them as materials for the limited application. They consider that their use is justified only in the case of the severely atrophied alveolar ridge, in obturators and epitheses. Conclusion: Resilient lining needs to be considered and planned in advance. It should not be used to compensate for errors in denture design. Appropriate selection of a material for the particular clinical case is of crucial importance.